ANALISIS PENERAPAN AKUNTANSI ASET TETAP PADA BADAN PENANGGULANGAN BENCANA DAERAH PROVINSI SULAWESI UTARA - Regel, Hendrykar Avaldo; Manossoh, Hendrik; Warongan, Jessy D.L (Universitas Sam Ratulangi, 2018)
Regional Disaster Management Agency of North Sulawesi Province is an Instance that is in the scope of the Government of the City of Manado and carry out the policy areas in the field of disaster relief of the region. Fixed assets is the most important part in carrying out its operational activities. Fixed assets are tangible assets that have benefits over period of 12 (twelve) months for use in kegitan Government or utilized by the general public. This research aims to study how the application of fixed assets Accounting on Regional disaster management agency of North Sulawesi province. Data collection methods used are interviews and studies library. Data analysis method used is descriptive qualitative. The results of this research show that the application of fixed assets Accounting on Regional disaster management agency of North Sulawesi province have not everything works in accordance with Government accounting standards PP 71-year 2010. For the valuation of fixed assets not yet in compliance with the applicable policy. but for classification, recognition, measurement, termination and deletion, disclosure and shrinkage were in accordance with the applicable policy.Keywords: Accounting, Fixed Assets, PSAP No.7